2019
DOI: 10.1515/cclm-2019-0204
|View full text |Cite
|
Sign up to set email alerts
|

Automated measurement of the erythrocyte sedimentation rate: method validation and comparison

Abstract: Background Development of automated analyzers for erythrocyte sedimentation rate (ESR) has imposed the need for extensive validation prior to their implementation in routine practice, to ensure comparability with the reference Westergren method. The aim of our study was to perform the analytical validation of two automated ESR analyzers, the Ves-Matic Cube 200 and the TEST1. Methods Validation was performed according to the recent International Council for Standardization in Hematology recommendations and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 26 publications
9
38
3
Order By: Relevance
“…Hereby, we demonstrated a much better precision of iSED with commercial control samples at both evaluated levels than in a previously published study, while patient samples yielded intrarun CVs similar to already reported data for iSED, with decreasing precision at medium and low ESR levels This is in concordance with data from a lot of validation studies of automated ESR analyzers, regardless of the analyzer type and measurement principle and can be attributed to small numbers rather than poor analytical performance, therefore not being considered clinically significant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Hereby, we demonstrated a much better precision of iSED with commercial control samples at both evaluated levels than in a previously published study, while patient samples yielded intrarun CVs similar to already reported data for iSED, with decreasing precision at medium and low ESR levels This is in concordance with data from a lot of validation studies of automated ESR analyzers, regardless of the analyzer type and measurement principle and can be attributed to small numbers rather than poor analytical performance, therefore not being considered clinically significant.…”
Section: Discussionsupporting
confidence: 90%
“…Still, we believe that, in the era of increased implementation of automated ESR systems, our study can be useful as a starting point for laboratory professionals that are willing to transit to the use of alternate ESR analyzers. Automation of ESR analysis is being attractive as it poses many advantages in comparison with the Westergren method, including analysis from the EDTA sample, easier manipulation and enhanced personnel safety, higher reproducibility of results, and availability of quality control …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy performance 8 of Novel ESR was evaluated by comparability 18 to the Reference WG and the comparative Modified WG for linearity 17 covering the AMI 19 . Reference WG and Novel ESR were measured from 271 samples and Modified WG from 240 samples and Passing‐Bablok regression analysis performed.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of fibrinogen as an additive was confirmed by correlation evaluation in clinical samples 20 . Inflammation markers were compared with the Reference WG 8 and their validity assessed 18 . The validity of the additive (fibrinogen) as an inflammation marker was assessed: 28 samples with CRP and fibrinogen, and 22 samples with albumin and globulin were selected as factors correlated with ESR measurement 21 .…”
Section: Methodsmentioning
confidence: 99%